2013
DOI: 10.1016/j.ijnt.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine dysfunction following traumatic brain injury in acute stage

Abstract: Aim Only few studies of hormonal dysfunction in acute setting after traumatic brain injury (TBI) are available in literature with variable results. The aim of the present study was to determine the incidence of anterior pituitary hormone deficiencies, and correlate with in hospital mortality. Methods This study was carried out on 30 patients with moderate to severe TBI presenting within 24 h of injury. Chemiluminiscence immunoassay using an automated chemiluminiscence analyser was used to determine the basal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…In the present study, the prevalence for the lowest cortisol cut‐off level of 83 nmol/L was 2.9%, almost identical with the prevalence reported in other studies …”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, the prevalence for the lowest cortisol cut‐off level of 83 nmol/L was 2.9%, almost identical with the prevalence reported in other studies …”
Section: Discussionsupporting
confidence: 92%
“…An association between acute post‐traumatic AI and mortality could not be shown in our study, in keeping with the work of Della Corte et al and Olivecrona et al and in contrast to Hannon et al . Nor could we confirm the work of Kakatti et al who showed a correlation between elevated cortisol levels of >23 μg/dL (634 nmol/L) and increased mortality . Nevertheless, the higher mortality seen in those of our patients with acute cortisol <276 nmol/L has influenced our recommendations for clinical care as shown below.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Studies have shown that increased sympathetic responses found in the young male population during the early phase of TBI which associated with adverse outcomes. 5 8) In our study, we tried to assess the effect of sedation (propofol versus midazolam) on stress response by measuring serum cortisol as a biomarker for stress response. However, we found a statistically significant reduction in mean cortisol levels in both groups after 48 hours of infusion, but the difference among groups was statistically insignificant.…”
Section: Discussionmentioning
confidence: 99%